The employment of polyphenol complexes extracted from Pеnthaphylloides fruticosa (L.) O. Scwarz for prophylactic of Coxsackie-virus infection - A. N. Evstropov; L. G. Burova; O. R. Greck; L. N. Zakharova; T. A. Volkhonskay (Бюллетень сибирской медицины, 2002)
In the present work the antiviral activity of water extract, received from Pеnthaphylloides fruticosa (L.) O. Scwarz, against Enteroviruses Coxsackie B (CVB) was studied. The maximal intoxic dose of the preparation for the cell-culture (CC) Нер-2 was 1500 mg/ml. It was found, that a preliminary processing of the CC by substance 24 hours before the virus contamination suppresses the virus reproduction in minimal inhibition doses 31 mg/ml — for CVB1-5 and 63 mg/ml — for CVB6. After that, the prophylactic action of the water extract against CVB3 was showed in experimental infection in newborn mice. It maximal intoxic doses for BALB/c mice is 100 mg/kg. The scheme with the preliminary inoculation of pregnant mice by 40 mg/kg of water extract within 3—5 days and following contamination of new-born animals by 100 DLM of virus, showed positive results: increase percent of survival and average life duration, improving of weight dynamics, decrease of virus accumulation level in tissues of brain, liver, heart. The received results determine good prospects for further investigation of water extract from Pеnthaphylloides fruticosa as prophylactic antiviral remedy.